Turkey's global governance strategies at the UN compared to the BRICS (2008–2014): clarifying the motivation–contribution nexus. Issue 9 (2nd September 2018) - Parlar Dal, Emel; Kurşun, Ali Murat
Abstract: This study attempts to analyse Turkey's contribution to the United Nations (UN) system in comparison with those of the Brazil, Russia, India, China, and South Africa (BRICS) countries between 2008 and 2014 on three levels: personnel, financial, ideational. Employing an integrated methodology of a global governance contribution index (GGCI) and statistical analysis of complementary raw data, this study empirically reveals the degree to which Turkey was able to transfer its capabilities into an effective contribution to the UN system on the three levels. Drawing on the findings of its quantitative analysis, this paper further qualitatively assesses the reasons behind the gap between Turkey's global governance motivations and its contribution to the UN system. In doing so, this study, first, deals with the main motivational drivers of its activism in global governance in the 2000s. After unpacking its integrated methodology, the second part of this study quantitatively compares Turkey's contribution to the UN system to that of the BRICS. The third part of this study delves into the main trends and deficiencies in Turkey's contribution to the UN system. Finally, this study concludes that Turkey, despite its high motivations for activism in global governance, has not performed well in transferring its capacities into contributions to the UN system, particularly on financial and personnel levels.